Pedagogical implications on curriculum support for learner progression: policy promises and outcomes - Mogale, Makobo Lydia (OpenED Network, 2023)
Part of enabling progressed learners’ successes is provision of adequate curriculum support to bridge content gap. Learner progression was introduced as an intervention for retention and to minimise school dropout. Dynamics around education policy implementation gaps seems to be obstacle between progression policy promises and outcomes. This is visible through the national grade 12 results which continue to decline amid learner progression. Within debates of progression policy derailing quality education, Covid19 disruptions unleashed inequalities in the education sector. For instance, learning losses and in turn pedagogical implications for progressed learners’ extended learning opportunities. This paper reports on curriculum support provided to progressed learners reflecting on Covid19 disruptions using Bandura’ Social Learning Theoretical lens. The study adopted a qualitative research approach placed within interpretivism paradigm and employed exploratory case study design. Six teachers were purposively selected from three secondary school in one district of the Limpopo Province, South Africa. Thus, two grade twelve teachers per school whose subjects were directly affected by progression policy because the study focuses on progression from grade eleven to twelve. Data were collected through document analysis and interviews. Thematic analysis was used for data analysis. Findings revealed limitations to reach out to progressed learners’ due catch-up plans because of lockdown and rotational models. This study concluded on a fair compliance on policy stipulations yet limited specific intervention strategies. The unique contribution of this study is the reflection on three implementation gaps which had implications for progression policy outcomes.
Keywords: Curriculum support; implementation; pedagogical implications; progression policy